The five lives of our cat Zook - Rocklin, Joanne (Laura Ann); 1978- 1906-1998. 1952- 1974- (New York Amulet Books, 2012)
As ten-year-old Oona and her younger brother conspire to break their sick cat Zook out of the veterinary clinic, Oona tells the story of Zook's previous lives.
Keywords: Cats -- Fiction; Family life -- Fiction; Fiction